Portuguese Contemporary Artists. - Arco 1987, Madrid; Art Basel 18'87; Contemporary Art Festival, Marca, Funchal, 1987 (Lisboa : Modulo - Centro Difusor de Arte, 1987)
Vidigal, Ana ; David, Ilda ; Botelho, Manuel ; Rosa, Manuel ; Casqueiro, Pedro ; Portugal, Pedro ; Saraiva, Pedro ; Rosengarten, ruth ; Costa, Victor ; Xana
Portuguese Contemporary Artists / Artistas Portugueses Contemporaneos, International Art Fairs: Arco 87, Madrid (Spain) and Art 18'87 Basel (Switzerland) and also the Contemporary Art Festival, Marca, Funchal (Madeira) which took place, respectively, from 12 to 17 february, from 17 to 22 June and from 3 to 9 September 1987.
boek
Keywords: Portugal